Growth of Soot Volume Fraction and Aggregate Size in 1D Premixed C2H4/Air Flames Studied by Laser-Induced Incandescence and Angle-Dependent Light Scattering. (1st October 2018) - Langenkamp, P. N.; van Oijen, J. A.; Levinsky, H. B.; Mokhov, A. V.
Abstract : The growth of soot volume fraction and aggregate size was studied in burner-stabilized premixed C2 H4 /air flames with equivalence ratios between 2.0 and 2.35 as function of height above the burner using laser-induced incandescence (LII) to measure soot volume fractions and angle-dependent light scattering (ADLS) to measure corresponding aggregate sizes. Flame temperatures were varied at fixed equivalence ratio by changing the exit velocity of the unburned gas mixture. Temperatures were measured using spontaneous Raman scattering in flames with equivalence ratios up toϕ = 2.1, with results showing good correspondence (within 50 K) with temperatures calculated using the San Diego mechanism. Both the soot volume fraction and radius of gyration strongly increase in richer flames. Furthermore, both show a nonmonotonic dependence on flame temperature, with a maximum occurring at ~1675 K for the volume fraction and ~1700 K for the radius of gyration. The measurement results were compared with calculations using two different semiempirical two-equation models of soot formation. Numerical calculations using both mechanisms substantially overpredict the measured soot volume fractions, although the models do better in richer flames. The model accounting for particle coagulation overpredicts the measured radii of gyration substantially for all equivalence ratios, although the calculated values improve atϕ = 2.35.